Effects of a healthy-eater self-schema and nutrition literacy on healthy-eating behaviors among Taiwanese college students. (14th November 2017) - Lee, Chia-Kuei; Liao, Li-Ling; Lai, I-Ju; Chang, Li-Chun
Abstract: Unhealthy eating behaviors contribute to obesity and chronic illness. This study examined the relative contributions of a healthy-eater self-schema (a self-conception as a healthy eater) and nutrition literacy on healthy-eating behaviors and whether nutrition literacy was a mediator among Taiwanese college students. A total of 1216 undergraduate students from six universities in Taiwan participated in the study from April to June 2016. Healthy-eating behaviors, nutrition literacy, healthy-eater self-schema and known determinants of eating behaviors (e.g. nutrition-related information, health status, nutrition knowledge needs, sex, year in college and residence) were measured by a self-report questionnaire. A hierarchical multiple regression and mediation analysis were conducted with the known determinants of eating behaviors as covariates. Results showed that a healthy-eater self-schema and nutrition literacy explained 9% and 12% of the variance in healthy-eating behaviors, respectively, and both had unique effects on healthy-eating behaviors. The effect of a healthy-eater self-schema on healthy-eating behaviors was partially mediated through nutrition literacy. Findings suggest that both a healthy-eater self-schema and nutrition literacy should be considered when promoting healthy-eating behaviors. Additionally, nutrition literacy interventions should be tailored to the healthy-eater self-schema status and emphasize the personal relevance of being a healthy-eater to improve the intervention's effectiveness.